2000
DOI: 10.1021/jp002591l
|View full text |Cite
|
Sign up to set email alerts
|

Field-Induced Photoluminescence Modulation of MEH−PPV under Near-Field Optical Excitation

Abstract: Electric field-induced modulation of the near-field photoluminescence of thin films of the conjugated polymer MEH-PPV was measured. A voltage bias applied between the near-field probe and the substrate results in a highly spatially confined electric field. The near-field photoluminescence intensity decreases when the sample bias is positive with respect to the probe while the intensity increases when the sample bias is negative. The modulation of photoluminescence intensity provides a sensitive measure of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 41 publications
(68 reference statements)
10
52
0
Order By: Relevance
“…Other studies by the Vardeny and Barbara groups have identified efficient luminescent quenching by polarons in PPV derivatives like DOO-PPV, 30 aggregates of a porphyrin derivative 31 and MEH-PPV. 32,33 In the latter case, 32 a Stern-Volmer quenching constant of 7ϫ10 Ϫ19 cm 3 was obtained, which implied that a single charge could quench over a thousand surrounding chromophores. Our quenching constant ␥ d is related to the Stern-Volmer constant K via…”
Section: Discussionmentioning
confidence: 92%
“…Other studies by the Vardeny and Barbara groups have identified efficient luminescent quenching by polarons in PPV derivatives like DOO-PPV, 30 aggregates of a porphyrin derivative 31 and MEH-PPV. 32,33 In the latter case, 32 a Stern-Volmer quenching constant of 7ϫ10 Ϫ19 cm 3 was obtained, which implied that a single charge could quench over a thousand surrounding chromophores. Our quenching constant ␥ d is related to the Stern-Volmer constant K via…”
Section: Discussionmentioning
confidence: 92%
“…Detailed studies of the time dynamics of ensemble fluorescence quenching,218 the concentration dependence in blends,219 and the morphology correlation using nearfield scanning optical‐probe techniques220 revealed that, under certain circumstances, electric fields can also amplify the fluorescence. This effect can result from field‐induced recombination from charge‐separated states.…”
Section: Single Polymer Chains In Devicesmentioning
confidence: 99%
“…McNeill et al [113,114] studied the near-field photoluminescence of thin-film MEH-PPV induced by a voltage bias applied between the near-field probe and the substrate. The goal was to investigate the field-induced modulation of the local carrier density.…”
Section: Near-field Scanning Optical Microscopy (Nsom)mentioning
confidence: 99%